نظرة قانون لاهاي الموحد لمعيار دولية عقد البيع - العياشي، شتواح (جامعة محمد لمين دباغين سطيف 2, 2014)
يكشف هذا البحث عن بعض الأحكام العامة لقانون لاهاي الموحد لسنة 1964 بشأن البيع الدولي للبضائع، زيادة على هذا يدرس مسألة جوهرية من مسائل القانون المادي الموحد لعقود البيع الدولي، والتي يتوقف عليها فتح الطريق لتطبيق قواعد مادية أعدت خصيصا للبيع الذي يتصف بالدولية. من خلال محاولة شرح معايير دولية عقود بيع البضائع التي اعتمدها.
This research reveals some of the general rules of The Hague uniform laws in 1964, which concern the international sale of goods In addition to that; it deals with a fundamental issue on the physical unified law of the international sale contracts upon which the way to the application of the rules, conducted for the intentional sale, is open. And this would be through the application of the criteria of the international sale of goods contracts that have been granted.
Keywords: القوانين والتشريعات -- قانون لاهاي الموحد -- عقود البيع -- البيع الدولي -- التجارة الدولية